A fatal acute appendicitis with sepsis and pneumonia was caused by melioidosis: a case report - Abu Tholib Aman; Yuli Mawarti; Agus Barmawi; Faisal Heryono; Rizka Humardewayanti Asdie (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2020)
We report anunderdiagnosed fatal case of melioidosis that involved dygestion system which complicated with pneumonia, and sepsis. The case was initially diagnosed as acute appendicitis, and subsequently the patient underwent an exploratory laparatomy and appendectomy. He was discharged afer 3 days of hospitalization. Thirty days afterward, he was admitted to another private hospital to experience another exploratory laparatomy with indication of pancreatitis, intra-abdominal organs adhesions, and postoperative enterocutaneous fistula (ECF), and hospitalized there for 25 days. He eventually suffered from sepsis, pneumonia, unclosed ECF, anemia, hypoalbuminemia, and electrolyte imbalance. He then referred to a tertiary teaching hospital and hospitalized there for a total 134 days until he passed away. His clinical condition was declining, despite a long course of broad spectrum antibiotics. Treatment delay, prolong hospitalization, and complications were the inevitable, although Burkholderia pseudomallei was finally identified 2 weeks prior to his death. This case highlight that melioidosis canassociate with acute appendicitis, and that the delay on its diagnosis and treatment may trigger complications and death.